The impact of green human resource management practices on organisational sustainability through green knowledge sharing - Aimun Khawaja; Khalida N. Janjua (SA Journal of Human Resource Management)
Orientation: This study investigated the linkage between Green Human Resource Management Practices (GHRMP) and organisational sustainability (OS).